Pathology Trainees Gain Clinical Pathology Experience as Lab Consultants Through Auditing Myeloid Mutation Panel Send-Out Tests: Hitting Two Birds With One Stone? - Hardy, Naomi L.; Jacobs, Jonathan; Mullins, Kristin; Christenson, Robert; Cox, Thoko; Murphy, Colin; Koka, Rima (Archives of Pathology & Laboratory Medicine, 2022)
Context.--: Inappropriate laboratory testing and the threat it poses to patient care and rising health care costs has become an important focus in the medical literature. Pathology residents, as physicians with an intimate knowledge of laboratory testing, may be uniquely equipped with the tools to intervene in situations of inappropriate testing and also benefit from lab use experience as part of their clinical pathology training. Objective.--: To employ a resident-driven initiative aimed at incorporating pathology residents as consultants for appropriate ordering of high-volume, send-out myeloid mutation panel testing. Design.--: During a 6-month study period, all myeloid mutation panel send-out tests were screened by senior pathology residents on their clinical chemistry rotation prior to approval at an academic medical center. A retrospective review of myeloid mutation panels from the prior 6 months was conducted with the same criteria to determine effectiveness of the intervention. Results.--: Of the 234 tests ordered during the study period, screening resulted in cancellation of 17% (n = 39), with proportional cost savings. The number of inappropriate orders successfully cancelled was significant compared with the preintervention period (control, 0%; intervention, 76.5%; P < .001, Fisher exact test). There was no significant difference in the proportion of inappropriate tests before and after intervention. Conclusions.--: Although test ordering patterns did not substantially change during the intervention period, pathology residents effectively reduced inappropriate myeloid mutation panel testing through prospective send-out auditing, leading to significant cost savings. Moreover, assessment of test use and appropriateness provided critical clinical pathology training within the areas of hematology, molecular genetics, and laboratory management.